Fabrication and Experimental Analysis of Geothermal Energy Resourses - Kumar Madheshiya, Sushil; R. Mishra, V.; sahu, Rohit; kumar sharma, Pradeep; tyagi, avdhesh (International Journal of Engineering and Technology, 2018)
This paper state that the practical approach of finding the utilization of geothermal energy resources we did fabrication and calculate all parameters. The objective is to design such a ventilation system in accordance with a geo thermal heat exchanger to cool or heat a room for human comfort with the lowest possible effect to the environment. This paper mainly have three stages first is to temperature measurement, second one is piping design and last one is fabrication.